Paixão da relação – paixão da falta - Müller, Hadwig Ana Maria (Revista Eclesiástica Brasileira, 2003)
O sofrimento dos pobres se associa muitas vezes a dons relacionais evidentes. O termo “paixão” expressa esse laço entre uma pobreza dolorosamente vivida e uma riqueza humana muitas vezes admirável. Esta experiência – relida aqui a partir da noção lacaniana de “falta” – encontra-se no coração da relação dos pobres para com Deus e de Deus para com os pobres. Mais ainda, ela está no coração de toda escuta, pois não há relação sem escuta, nem escuta sem desejo, e, então, sem falta. A partir disso, deixando-nos guiar pela revelação bíblica acolhida na fé, é possível pressentir algo da vida íntima de Deus, viver diferentemente nossas relações humanas e o dinamismo da missão sobre a base de uma inteligência renovada de Igreja-comunhão. Abstract: The suffering of the poor often brings in its wake a clear gift for human relations. The term “passion” expresses this connection between a painfully endured poverty and a – sometimes astonishing – human richness. This experience – examined here in the light of the Lacanian concept of “manque” – can be found in the relationship between the poor and God and between God and the poor. Moreover, this experience is at the core of every act of listening, for there is no relationship without listening, no listening without desire and no desire without “manque”. With this in mind, a re-reading of the Bible can help us to have a better understanding of God’s intimate life and, through this, to experience our human relations differently. It can also give us a new insight into the dynamics of a mission that has as basis a renewed vision of the Church as communion.